2020
DOI: 10.1186/s13256-020-02485-8
|View full text |Cite
|
Sign up to set email alerts
|

Epithelioid trophoblastic tumor coexisting with choriocarcinoma around an abdominal wall cesarean scar: a case report and review of the literature

Abstract: Background Mixed gestational trophoblastic neoplasms are extremely rare and comprise a group of fetal trophoblastic tumors including choriocarcinomas, epithelioid trophoblastic tumors, and placental site trophoblastic tumors. We present a case of a patient with extrauterine mixed gestational trophoblastic neoplasm adjacent to the abdominal wall cesarean scar. On the basis of a literature review, this type of case has never been reported before due to the unique lesion location and low incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…Although ETT was recognized as a distinct GTN entity in 1998 by Shih and Kurman (2), ETTs combined with other gestational trophoblastic have been reported. MGTNs are extremely rare, and a review of English literature revealed that in addition to our case, there are 36 other MGTDs (Table 1) (2)(3)(4)6,(8)(9)(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 52%
“…Although ETT was recognized as a distinct GTN entity in 1998 by Shih and Kurman (2), ETTs combined with other gestational trophoblastic have been reported. MGTNs are extremely rare, and a review of English literature revealed that in addition to our case, there are 36 other MGTDs (Table 1) (2)(3)(4)6,(8)(9)(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 52%
“…We found only a few reports of ETT presenting as a mass in the Caesarean scar, with two being synchronous with choriocarcinoma [6][7][8][9][10]. Black et al reported a similar case where the patient with three previous Caesarean sections had been diagnosed with ETT after being followed for spontaneous abortion with retained products of conception [6].…”
Section: Discussionmentioning
confidence: 97%
“…Distinctive of PSTTs, the histological image of ETT shows well-circumscribed, nested growth of smaller cells with less nuclear pleomorphism, often presented with a geographical necrosis pattern. As there are reports of ETT coexisting with PSTT [7], it is necessary to distinguish these two entities histologically. Furthermore, postchemotherapy examined samples of other forms of GTN can present with a histological pattern similar to ETT [17].…”
Section: Discussionmentioning
confidence: 99%
“…Xing et al [ 3 ] first reported that ETT has a low probability of occurring in the ovary and fallopian tube, simultaneously. The composition of the fallopian tube tumor in our case study is the same as that on the ovary and it may be the metastasis of ovarian ETT, common in women of childbearing age after various pregnancies[ 4 , 5 ]. The patient was 29-years-old in 2015 and due to partial hydatidiform mole surgery, the blood β-hCG value decreased slowly for 3 mo and the uterine cavity presented an abnormal echo.…”
Section: Discussionmentioning
confidence: 99%